A Coxsackievirus B vaccine protects against virus-induced diabetes in an experimental mouse model of type 1 diabetes - Stone, Virginia M. (Diabetologia, 2017)
AIMS/HYPOTHESIS: Epidemiological studies suggest a role for Coxsackievirus B (CVB) serotypes in the pathogenesis of type 1 diabetes, but their actual contribution remains elusive. In the present study, we have produced a CVB1 vaccine to test whether vaccination against CVBs can prevent virus-induced diabetes in an experimental model. METHODS: NOD and SOCS1-tg mice were vaccinated three times with either a formalin-fixed non-adjuvanted CVB1 vaccine or a buffer control. Serum was collected for measurement of neutralising antibodies using a virus neutralisation assay. Vaccinated and buffer-treated mice were infected with CVB1. Viraemia and viral replication in the pancreas were measured using standard plaque assay and PCR. The development of diabetes was monitored by blood glucose measurements. Histological analysis and immunostaining for viral capsid protein 1 (VP1), insulin and glucagon in formalin-fixed paraffin embedded pancreas was performed. RESULTS: The CVB1 vaccine induced strong neutralising antibody responses and protected against viraemia and the dissemination of virus to the pancreas in both NOD mice (n = 8) and SOCS1-tg mice (n = 7). Conversely, 100% of the buffer-treated NOD and SOCS1-tg mice were viraemic on day 3 post infection. Furthermore, half (3/6) of the buffer-treated SOCS1-tg mice developed diabetes upon infection with CVB1, with a loss of the insulin-positive beta cells and damage to the exocrine pancreas. In contrast, all (7/7) vaccinated SOCS1-tg mice were protected from virus-induced diabetes and showed no signs of beta cell loss or pancreas destruction (p < 0.05). CONCLUSIONS/INTERPRETATION: CVB1 vaccine can efficiently protect against both CVB1 infection and CVB1-induced diabetes. This preclinical proof of concept study provides a base for further studies aimed at developing a vaccine for use in elucidating the role of enteroviruses in human type 1 diabetes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00125-017-4492-z) contains peer-reviewed but unedited supplementary material, which is available to authorised users.